Poor agreement between predictive equations of energy expenditure and measured energy expenditure in critically ill acute kidney injury patients - De Góes, Cassiana R. [UNESP]; Berbel-Bufarah, Marina N. [UNESP]; Sanches, Ana Claudia S. [UNESP]; Xavier, Patrícia S. [UNESP]; Balbi, André L. [UNESP]; Ponce, Daniela [UNESP] (Karger Publishers, 2016)
Background: There are multiple equations for predicting resting energy expenditure (REE), but how accurate they are in severe acute kidney injury (AKI) patients is not clear. Our aim was to determine if predictive equations for estimated REE accurately reflect the requirements of AKI patients. Methods: We included in this prospective and observational study AKI patients AKIN-3 assessed by indirect calorimetry (IC). Bland-Altman, intraclass correlation coefficient and precision (percentagem of predicted values within 10% of measured values) were performed to compare REE by equations with REE measured by IC. Results: IC was applied in 125 AKI patients. The mean age was 62.5 ± 16.6 and 65.6% were male. Mean REE measured was 2,029.11 ± 760.4 kcal/day. There were low precision, and poor agreement between measured and predicted REE by the Harris-Benedict (HB), Mifflin, Ireton-Jones, Penn state, American College of Chest Physicians, and Faisy equations. HB without using injury factor was the least precise (18% of precision). Modified Penn state equation had the best precision, although the precision rate was only 41%. For all equations, the limits of agreement range were large leading to the potential under or overfeeding of individual patients. Conclusion: None of these equations accurately estimated measured REE in severe AKI patients and most of them underestimated energy needs.
Keywords: Acute kidney injury; Energy expenditure; Indirect calorimetry